2019
DOI: 10.1029/2018ja026291
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Electron Precipitation: Multievent Analysis of Its Spatial Extent During EMIC Wave Activity

Abstract: Electromagnetic ion cyclotron (EMIC) waves can drive precipitation of tens of keV protons and relativistic electrons, and are a potential candidate for causing radiation belt flux dropouts. In this study, we quantitatively analyze three cases of EMIC-driven precipitation, which occurred near the dusk sector observed by multiple Low-Earth-Orbiting (LEO) Polar Operational Environmental Satellites/Meteorological Operational satellite programme (POES/MetOp) satellites. During EMIC wave activity, the proton precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 78 publications
6
74
0
Order By: Relevance
“…While precipitating protons can produce proton aurora Yuan et al, 2010),~MeV electrons can interact with atmospheric nitrogen and hydrogen oxides, leading to ozone reduction (e.g., Meraner & Schmidt, 2018). The efficacy of EMIC waves in scattering MeV electrons and ring current protons has been confirmed in multiple studies, both observationally and theoretically (Blum et al, 2015;Capannolo et al, 2018Capannolo et al, , 2019Hirai et al, 2018;Qin et al, 2018Qin et al, , 2019Shekhar et al, 2017;Woodger et al, 2018;Yuan et al, 2018). However, the techniques and the satellites used have limitations that still leave a few open questions, for example, on the minimum energy of electrons (E min ) that can be scattered into the loss cone.…”
Section: 1029/2019gl084202mentioning
confidence: 96%
“…While precipitating protons can produce proton aurora Yuan et al, 2010),~MeV electrons can interact with atmospheric nitrogen and hydrogen oxides, leading to ozone reduction (e.g., Meraner & Schmidt, 2018). The efficacy of EMIC waves in scattering MeV electrons and ring current protons has been confirmed in multiple studies, both observationally and theoretically (Blum et al, 2015;Capannolo et al, 2018Capannolo et al, , 2019Hirai et al, 2018;Qin et al, 2018Qin et al, , 2019Shekhar et al, 2017;Woodger et al, 2018;Yuan et al, 2018). However, the techniques and the satellites used have limitations that still leave a few open questions, for example, on the minimum energy of electrons (E min ) that can be scattered into the loss cone.…”
Section: 1029/2019gl084202mentioning
confidence: 96%
“…These waves drive considerable contemporary scientific interest, particularly during the recent Van Allen Probes mission. Many recent studies are dedicated to the loss they cause to ultrarelativistic electrons (e.g., Thorne & Kennel, ; Albert, ; Jordanova et al, ; Miyoshi et al, ; Rodger et al, , Rodger et al, ; Li et al, , 2014; Usanova et al, , ; Kersten et al, ; Blum et al, ; Clilverd et al, ; Woodger et al, , ; Colpitts et al, ; Shprits et al, , , , ; Hendry et al, , ; Zhang et al, ; Aseev et al, ; Drozdov, Shprits, Usanova, et al, ; Capannolo et al, , ; Denton et al, ; Qin et al, ), themselves related to the complex location and duration of these waves. EMIC waves are discrete electromagnetic emissions in multiple frequency bands (e.g., Saikin et al, ), which are observed across a large region of geospace (e.g., Saikin et al, ), including the ring current and the plasmasphere, dayside plumes, and the outer dayside magnetosphere (Engebretson et al, ; Engebretson et al, ; Engebretson et al, ; Tetrick et al, ).…”
Section: Particle Loss In the Inner And Outer Zonesmentioning
confidence: 99%
“…For example, Clilverd et al () showed EMIC‐induced electron precipitation with a lower cutoff energy of 280 keV. Other conjunction events have also demonstrated sub‐MeV electron precipitation driven by EMIC waves (e.g., Capannolo, Li, Ma, Shen, et al, , Capannolo, Li, Ma, Chen, et al, ; Hendry et al, ).…”
Section: Introductionmentioning
confidence: 99%